PEMBERDAYAAN PEREMPUAN NELAYAN BERBASIS PELATIHAN DIVERSIFIKASI OLAHAN IKAN CAKALANG DAN PUPUK ORGANIK LIMBAH IKAN CAKALANG DI DESA LABUAN SALUMBONE KECAMATAN LABUAN KABUPATEN DONGGALA - Mawar, Mawar; Rosdiana, Rosdiana; Supriaty, Rika; Sosiawati, Emma (Universitas Mataram, 2025)
The transformation of simple technology through the empowerment of women fishers in processing fish catches into value-added products is essential to be developed. Diversification of fish-based products, such as the production of fish meatballs, fish nuggets, fish bone crackers, and the utilization of fish waste into organic fertilizer, can enhance skills while also creating new economic value. The current condition of Labuan Salumbone Village shows a high dependency on traders from outside the village, particularly from Palu City, to fulfill snack needs such as meatballs and nuggets, with food safety and hygiene still uncertain. Meanwhile, fish waste remains a problem as it is often discarded, causing unpleasant odors and polluting the coastal environment. Through the Community Service Program of Alkhairaat University, a solution is offered in the form of training on skipjack tuna product diversification. The program is carried out over three days, beginning with socialization, followed by training in product making (meatballs, nuggets, bone crackers, and organic fertilizer), and continued with field mentoring and monitoring. The training methods include both technical education on product processing and non-technical education on entrepreneurship management. The main problems faced by the village are the low skills of women fishers in fish processing, unstable household income due to uncertain fish catches, and high unemployment caused by dependence on formal employment. Through this training, women fishers are expected to acquire new skills, create micro-businesses, and strengthen household economic independence. In addition, the processing of fish waste into environmentally friendly organic fertilizer is expected to maintain coastal cleanliness. The sustainability of the program will be ensured through monitoring, evaluation, and institutional support from the village authorities.